2006
DOI: 10.1002/jcu.20225
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fluid intake on renal length measurement in adults

Abstract: Oral fluid intake causes a statistically significant increase in renal length. This observation should be taken into consideration when renal length measurements are clinicallly important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Renal length and cortical thickness are routine measurements in the diagnosis and follow‐up of most disease conditions involving the kidneys 4 – 7 . Kantarci et al 8 showed that renal length measurements might increase after oral fluid intake. In an MR urographic study, renal length changes after diuretic injection, which has effects similar to those of hydration on kidneys, were shown to be correlated with renal function 3 …”
mentioning
confidence: 99%
“…Renal length and cortical thickness are routine measurements in the diagnosis and follow‐up of most disease conditions involving the kidneys 4 – 7 . Kantarci et al 8 showed that renal length measurements might increase after oral fluid intake. In an MR urographic study, renal length changes after diuretic injection, which has effects similar to those of hydration on kidneys, were shown to be correlated with renal function 3 …”
mentioning
confidence: 99%
“…We read with great interest the article entitled "The effect of fluid intake on renal-length measurement in adults" by Kantarci et al [1]. The authors have statistically made clear that the intake of oral liquid by adults shows profound increase (approximately 7%) in kidney length.…”
Section: Sirsmentioning
confidence: 96%
“…The authors have statistically made clear that the intake of oral liquid by adults shows profound increase (approximately 7%) in kidney length. Furthermore, the effect of oral-liquid intake of abnormal or diseased kidneys is unknown and needs researching [1].…”
Section: Sirsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oni, takođe, opisuju značajno opadanje apsolutne i relativne dužine bubrega i kod muška-raca i kod žena posle 60. godina života i u zaključku ističu da u ovom dobu određivanje relativne dužine bubrega nije od primarnog značaja zbog uticaja pola, telesne visine i starenja [13]. U novijoj literaturi je naznačena i greška koja se čini ako se pristupi merenju dužine bubrega kod ispitanika neposredno posle ekscesivnog unosa tečnosti, pa je s tim u vezi izračunato da bubrezi u tom slučaju pokazuju za oko 7% veću dužinu [14], što bi trebalo izbeći tokom ispitivanja veličine bubrega. Takođe, opisan je i uticaj prevremenog rođenja (pre navršene 32 nedelje gestacije) koje će uticati na smanjenje dužine bubrega i broja nefrona kod mladih adultnog doba, što može uticati na validnost rezultata istraživanja [15].…”
Section: Relative Length Of Left Kidney Of Men and Womenunclassified